Self-reliant transcendentalism in five modern American nonfiction texts - Brits, Jason (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2017)
This thesis is concerned with the persistence of Self-Reliant Transcendentalist thought in modern American nonfiction. It traces the ideas of Ralph Waldo Emerson and Henry David Thoreau (as progenitors of the Self-Reliant strand of the Transcendentalist movement in America) in the patterns of thought and endeavours of individuals as documented in five notable nonfiction texts published between 1968 and 2013. The texts are Edward Abbey's Desert Solitaire, Annie Dillard's Pilgrim at Tinker Creek, Jon Krakauer's Into the Wild, Elizabeth Gilbert's The Last American Man, and Will Harlan's Untamed: The Wildest Woman in America and the Fight for Cumberland Island. Each of the seemingly Romantic individuals portrayed in these texts not only seeks to live a life similar to that of Thoreau during his famous sojourn at Walden Pond, but also seems to embody some of Emerson's and Thoreau's key Transcendentalist ideas. These modern and contemporary individuals, and the way in which they are portrayed in texts that fall under the general rubric of "creative nonfiction," are testament to the continuing relevance of Transcendentalist thought in the United States - and in Western society more generally, as it seeks to negotiate a new relationship with Nature in the shadow of massive impending ecological disaster.
Keywords: Transcendentalism in literature; Self-reliance in literature; Creative nonfiction, American -- History and criticism; Abbey, Edward, 1927-1989 -- Desert solitaire; Krakauer, Jon -- Into the wild; Gilbert, Elizabeth, 1969- -- The last American man; Harlan, Will -- Untamed: the wildest woman in America and the fight for Cumberland Island; Emerson, Ralph Waldo, 1803-1882; Thoreau, Henry David, 1817-1862